Racketeering in religion: Adorno and evangelical support for Donald Trump. (December 2018) - Brittain, Christopher Craig
In the 2016 American presidential election, 81% of White evangelicals voted for Donald Trump despite the obvious fact that he had little knowledge or interest in Christianity. This has continued to puzzle many commentators, as well as conservative Christian leaders. This paper argues that Theodor W. Adorno's 1943 analysis of the radio broadcasts of Martin Luther Thomas provides insight into Trump's popularity among evangelicals. Adorno compares the fascist-style broadcasts of Thomas to a pagan religious sect. He describes this practice as "racketeering in religion, " which effectively results in the "liquidation of religion." The article demonstrates ways in which this analysis is relevant for understanding the relationship between Trump and American Evangelicals.